Planes Crazy: Transformations of Pictorial Space in 1930s Cartoons - Crafton, Donald (Cinémas, 2005)
Abstract It is apparent from viewing the short films produced by the Disney studio in the 1930s that the concepts of pictorial space changed dramatically during the decade. All the major studios experimented with increasing the three-dimensionality of their compositions. The motivation may have been to produce films that complemented, rather than contrasted with, the visual norms of the feature films they accompanied on film programs. This article looks at the spatial innovations and evidence of new techniques found in the films of Disney and competing studios.